Patients' Satisfaction towards the Treatment and Awareness of Health Facilities in the Hospital - Thapa, Sonu; Nyaupane, Prativa (NPRC Journal of Multidisciplinary Research, 2024)
Patient satisfaction is a critical indicator of healthcare quality, reflecting the extent to which medical services meet or exceed patient expectations. In a rapidly evolving healthcare landscape, understanding patients' satisfaction with treatment and their awareness of available health facilities is vital for enhancing service delivery. This study aims to assess the level of satisfaction among patients regarding treatment and their awareness of hospital facilities in private hospitals of Kathmandu Valley. A quantitative research approach was employed, utilizing a descriptive research design and convenience sampling to collect data from 116 respondents aged 15 to over 30 years. Data were gathered through a structured questionnaire consisting of socio-demographic details and questions about patient satisfaction and awareness. The findings reveal that a significant majority of patients express high satisfaction with physicians’ communication, diagnostic accuracy, and treatment processes, with 92.2% reporting health improvements following hospital visits. Emergency care and attentiveness to critical cases were highly rated, while perceptions regarding gender differentiation in treatment showed variability, highlighting areas for improvement. The study concludes that while overall patient satisfaction is high, efforts to address gaps in equitable treatment practices and enhance awareness of health facilities are necessary. The novelty of this research lies in its focus on integrating socio-demographic variables with patient satisfaction metrics to provide a comprehensive understanding of healthcare service delivery in the context of Kathmandu Valley.